MATERIAL DESIGN OF HIGHLY-SELECTIVE ADSORBENT FOR SEPARATION OF LYMPHOCYTE SUBPOPULATIONS - NAGOYA, M.; YAMAMOTO, Y.; YURA, H.; AKAIKE, T.; TAKAHASHI, A. (Jinko Zoki, 1990)
Adhesiveness of lymphocyte subpopulations to the adsorbents with affinity substances was investigated for carrying out therapy such as cytapheresis, LAK, transplantation or immunological diagnosis. B lymphocytes adhered selectively to the adsorbents with polysaccharides containing abandant hydrogen bonding sites, and T lymphocytes (CD4 (+) and CD8 (+) cells) were preferentially attached to the adsorbents immobilizing glycolipids via hydrophobic bond.